Opal (Zn/Si) ratios as a nearshore geochemical proxy in coastal Antarctica - Hendry, K; Rickaby, R (Paleoceanography, 2016)
During the last 50 years, the Antarctic Peninsula has experienced rapid warming with associated retreat of 87% of marine and tidewater glacier fronts. Accelerated glacial retreat and iceberg calving may have a significant impact on the freshwater and nutrient supply to the phytoplankton communities of the highly productive coastal regions. However, commonly used biogenic carbonate proxies for nutrient and salinity conditions are not preserved in sediments from coastal Antarctica. Here we describe a method for the measurement of zinc to silicon ratios in diatom opal, (Zn/Si)opal, which is a potential archive in Antarctic marine sediments. A core top calibration from the West Antarctic Peninsula shows (Zn/Si)opal is a proxy for mixed layer salinity. We present down-core (Zn/Si)opal paleosalinity records from two rapidly accumulating sites taken from nearshore environments off the West Antarctic Peninsula which show an increase in meltwater input in recent decades. Our records show that the recent melting in this region is unprecedented for over 120 years. Copyright 2008 by the American Geophysical Union.